EDUCATION ON ADDICTIVE AND ADDICTIVE SUBSTANCES AND EXPERIMENTS: THE DANGERS OF SMOKING TO HEALTH - Mete, Yuliana Yenita; Gago, Jumilah; Ota, Maria Kristina; Nisa, Fadhila Chairul; Keke, Adolfin; Da Jeen, Maria Nggara Jaru; Hayon, Melkior Bala; Leraboleng, Novensianus; Gene, Agustina Tiara (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Adolescent smokers are a group particularly vulnerable to the negative effects of addictive and addictive substances in cigarettes, such as nicotine and tar. Limited understanding of the risks of smoking increases the likelihood of becoming active smokers or being affected by passive smoking and third-hand smoke. The Student Creativity Program was conducted at SMP Adhyaksa Ende, aiming to enhance students’ knowledge about the dangers of smoking through a simple and interactive practical approach. The activities included an initial presentation, a practicum demonstration using a plastic bottle filled with water with holes on the top and bottom, where a small pipe was installed at the bottom hole. Cotton at the bottle mouth served as a filter, while a cigarette was placed in the top hole to demonstrate the release of harmful substances. During the session, students were actively engaged through question-and-answer discussions regarding the effects of nicotine, tar, and passive smoking risks, making the learning process interactive. The results showed increased student awareness of smoking risks, their ability to identify harmful substances in cigarette smoke, and visual understanding of smoke dispersion and filtration. The discussion emphasizes the importance of combining demonstrative, participatory, and interactive methods to strengthen adolescents’ understanding and develop critical attitudes toward smoking. In conclusion, this PKM effectively conveyed information on addictive and addictive substances, enhanced student engagement, and fostered preventive awareness. Recommended follow-up actions include repeating the program in other classes, integrating adolescent health education into the school curriculum, and developing interactive educational modules based on simple practicums to sustain awareness of smoking hazards.